Solar-Driven Carbon Dioxide Reduction: A Fair Evaluation of Photovoltaic-Biased Photoelectrocatalysis and Photovoltaic-Powered Electrocatalysis - Zhang, Ying; Ye, Conglin; Duan, Jingjing; Feng, Hao; Liu, Dong; Li, Qiang (Frontiers in Energy Research, 2022)
The salient question addressed in this work is whether and how photovoltaic-biased photoelectrocatalysis (PV-PEC) can fairly and practically be as competitive as photovoltaic-powered electrocatalysis (PV-EC) for solar-driven carbon dioxide reduction (CO2RR). It was argued that to fairly evaluate PV-PEC and PV-EC CO2RR approaches in terms of techno-economy, the two devices should be driven by the same PV cell and produce the same group of products for the same series of Faradaic efficiency for each product. For this condition, PV-PEC CO2RR was shown to surprisingly have higher solar-to-chemical (STC) energy conversion efficiency than PV-EC. Results show that the STC efficiency of 8%, double the state-of-the-art efficiency, is achievable for PV-PEC CO2RR that employs low-cost perovskite PV cell and silicon PEC photocathode. This non-trivial performance was achieved by leveraging novel design of light management. In particular, the proposed reflective-spectrum-splitting light management configuration enables the use of high-efficiency opaque perovskite PV cell, which significantly boosts the efficiency of PV-PEC CO2RR. Furthermore, the framework generalized in this work is also applicable to other solar-driven catalytic processes with various different products such as productions of H2O2 by water oxidation and ammonia by nitrogen fixation.